INDONESIAN WOMEN ELECT: THE STUDY OF ISLAMIC PHILOSOPHY - Teguh Teguh; Iffatin Nur (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2022)
Women's participation in Indonesian politics gives its own color for the democracy of the nation. The number of female voters in the DPT of General Election 2019 is greater than the number of male voters, becoming an important key to the future direction of Indonesia's politics, democracy, and governance. This causes women's voices to become significantly valuable as the entry gate for the struggle and the development of the face of Indonesian politics, democracy, and governance. In this study, descriptive qualitative method was used with the Secondary Data Analysis (ADS) approach which utilized secondary data as the main research data related to the phenomenon of women's choice in the 2019 Presidential Election. The main objective of the current research is to see and analyze the level of adherence, pragmatism, fanaticism, and political intelligence of Indonesian women in making decisions to give their vote in the Presidential Election 2019 in a philosophical study. In terms of democratic presidential elections, philosophically if we believe in a democratic system as a form of sovereignty in the hands of the people, it is appropriate that the people directly elect the executive authorities, which in this case are the president and vice president. The elected president and vice president will further be responsible for the people who choose them, in this case is taking care, protecting, and guaranteeing the welfare of all people, including women. Therefore, there are several factors behind women's decisions in determining or voting which pair of president and vice president they think is ideal.